November Blues - Draper, Sharon M. (Sharon Mills) (New York : Atheneum Books for Young Readers, 2007)
A teenaged boy's death in a hazing accident has lasting effects on his pregnant girlfriend and his guilt-ridden cousin, who gives up a promising music career to play football during his senior year in high school.
012 up.
Keywords: Pregnancy -- Fiction; High schools -- Fiction; School stories; African Americans -- Fiction